How does inventory performance affect operational performance? An example from U.S. space vehicles and aircraft parts industries - Hancerliogullan, Gulsah; Koksalmis, Emrah; Calisir, Fethi (IEEE, 2017)
Inventory management is in the heart of operational performance in aircraft parts and space vehicles industries. As a result of its importance in practice, this subject has been extensively studied in recent years in operations management. The main focus of this study is to look at the relationship between inventory management performance such as inventory effectiveness, efficiency and responsiveness and company operational performance. A performance model, which includes the different dimensions of aircraft parts and space vehicle industries' inventory management system, has been applied and empirically tested. In order to examine the effect of various measures on inventory performance, the regression analysis has been employed. We use financial data of 39 publicly listed U.S. aircraft parts and space vehicle industries for the 11-year period, 2005 to 2015. The data (Compustat North America Annually Updated) is taken from Standard &Poor's Compustat database via Wharton Research Data Services (WRDS). We discuss the implementation of these experimental results on the study of inventory management policy execution, and give researchers some guidance for further research areas.